Hubungan Dukungan Sosial Dengan Self-Efficacy Pada Ibu Menyusui Yang Bekerja - Hapsari, Qanaya Ratih; Sarajar, Dewita Karema (Universitas Mataram, 2024)
Breastfeeding mothers who work face their own set of challenges during the breastfeeding process. Breastfeeding while working is not to be underestimated, especially in the absence of social support and self-efficacy among mothers. Support from coworkers emerges as one of the factors that can enhance self-efficacy among breastfeeding mothers. Such support can aid mothers in overcoming the challenges they face while breastfeeding. The aim of this research is to ascertain the relationship between social support and self-efficacy among working breastfeeding mothers. The approach employed in this research is a quantitative correlational approach with a sample size of 97 respondents. The sampling technique utilized in this research is non-probability sampling. Data analysis results indicate a correlation coefficient of r = 0.583, suggesting a positive relationship between social support and self-efficacy. This implies that higher levels of social support correspond to higher levels of self-efficacy among working breastfeeding mothers.